Evaluation of Different Fungicides and their Compatibility with Potential Trichoderma spp. for the Management of Aspergillus niger, Incitant of collar rot of Groundnut - Nandeesha, B.S.; Kumar, M. Reddi; Reddy, N.P.Eswara (Asian Journal of Biological and Life Sciences, 2013)
Among the 14 isolates of Trichoderma spp. TAG-2, TAG-10, TAG-13 were characterized as very fast growing, while TAG-14, TAG-11 and TAG-7 are fast growing and remaining were moderate growing. In dual culture technique, the isolates TAG-2, TAG-13 and TAG-10 have shown maximum inhibition percentage of 81.36, 78.51 and 75.97 against the test pathogen Aspergillus niger while, the least inhibition percentage of 63.24 was observed in the isolate, TAG-9. In vitro efficacy of four systemic fungicides viz., carbendazim, propiconazole, tebuconazole and hexaconazole and two non-systemic fungicides viz., mancozeb and captan, were evaluated against A. niger at 250, 500, 1000 and 1500ppm concentrations. All systemic fungicides were found highly effective and completely inhibited the mycelial growth of the pathogen even at 250ppm followed by mancozeb. Out of four systemic fungicides and two non systemic fungicides tested under in vitro for compatibility with potential bioagent, mancozeb was found highly compatible with TAG-2. An integrated management strategy was developed for collar rot of groundnut under glass house conditions. Out of 12 treatment combinations, maximum disease reduction was achieved by integrated use of seed treatment with mancozeb @ 2g/kg + soil application with effective fungal antagonist TAG-2 @ 8g/kg (T10 ) as this treatment recorded PDI of 7.16 percent. This treatment not only reduced the disease incidence to a maximum extent, but also recorded maximum plant height (37.64cm), root length (28.50cm) and maximum dry weight of shoot (6.84gm) and root (0.71gm) of groundnut when compared to all other treatments.